2007
DOI: 10.1007/s11306-007-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiles of interacting mycelial fronts differ for pairings of the wood decay basidiomycete fungus, Stereum hirsutum with its competitors Coprinus micaceus and Coprinus disseminatus

Abstract: The paper presents the first proof-of principle study of metabolite profiles of the interacting mycelial fronts of a wood decomposer basidiomycete, Stereum hirsutum, paired with two competitor basidiomycetes, Coprinus disseminatus and C. micaceus, using TLC and GC-TOF-MS profiling. GC-TOF-MS profiles were information rich, with a total of 190 metabolite peaks detected and more than 120 metabolite peaks detected per sample. The metabolite profiles were able to discriminate between the interactions of S. hirsutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 29 publications
3
59
2
2
Order By: Relevance
“…Ecometabolomics provides a useful approach to the understanding of the mechanisms underlying competitive relationships. For example, as we have discussed earlier, Peiris et al (2008), in a ecometabolomic study of the competition among three different fungus species competing during wood decomposition, reported that 2-methyl-2,3-dihydroxypropionic acid and pyridoxine are synthesized by some fungi to inhibit the growth of their direct competitors. Thus, the competitive advantage that could be attributed to simply a greater growth capacity of one species compared to the others is in fact linked, at least partially, to a chemical growth suppression of the competitor species.…”
Section: More On Biotic Relationshipsmentioning
confidence: 85%
See 1 more Smart Citation
“…Ecometabolomics provides a useful approach to the understanding of the mechanisms underlying competitive relationships. For example, as we have discussed earlier, Peiris et al (2008), in a ecometabolomic study of the competition among three different fungus species competing during wood decomposition, reported that 2-methyl-2,3-dihydroxypropionic acid and pyridoxine are synthesized by some fungi to inhibit the growth of their direct competitors. Thus, the competitive advantage that could be attributed to simply a greater growth capacity of one species compared to the others is in fact linked, at least partially, to a chemical growth suppression of the competitor species.…”
Section: More On Biotic Relationshipsmentioning
confidence: 85%
“…Competition Peiris et al (2008), using GC-MS partial ecometabolomics of polar metabolites, have studied the mycelial tissues of three competing fungus species during wood decomposition. They observed that the synthesis of 2-methyl-2,3-dihydroxypropinoic and pyridoxine acids can be involved in defensive mechanisms activated in response to direct contact between the mycelia of the different fungus species studied, thus showing the importance of exudated metabolites as resources for chemical defense in direct competition for space and sources.…”
Section: Plant-animalmentioning
confidence: 99%
“…In this study, 127 different metabolites were identified and measured based on GC-TOF-MS. Second, detecting the changes in the important metabolites at different time points could assist in elucidating the roles of these metabolites in the modulation dynamics of the ecosystem. Third, the chemical composition of the environment (i.e., agar) could also be monitored to reveal metabolic cooperation due to its role in metabolite exchanges (15,24). Research on metagenomics and metaproteomics usually deduced the role of some organism in the ecosystem based on gene or protein analysis, but the metabolomics approach would provide a more intuitive understanding of how cells interact with each other via metabolites and the cellular responses to environments.…”
Section: Discussionmentioning
confidence: 99%
“…This said, some are clearly intended to send signals (including cytotoxic molecules) to other organisms, and many examples (e.g. [166]) are known in which the presence of organism 1 indices organism 2 to synthesise molecules that are normally cryptic. In enclosed environments, a molecule that is secreted and promotes both its own synthesis and secretion in another cell of the same species can achieve a steady-state concentration of the pheromone that depends on the concentration of cells.…”
Section: Why Would Microbes Excrete Expensively Produced Biochemicals?mentioning
confidence: 99%